Chemotherapy-induced monoamine oxidase expression in prostate carcinoma functions as a cytoprotective resistance enzyme and associates with clinical outcomes. - Ryan R Gordon; Mengchu Wu; Chung-Ying Huang; William P Harris; Hong Gee Sim; Jared M Lucas; Ilsa Coleman; Celestia S Higano; Roman Gulati; Lawrence D True; Robert Vessella; Paul H Lange; et al. (PLoS ONE, 2014)
To identify molecular alterations in prostate cancers associating with relapse following neoadjuvant chemotherapy and radical prostatectomy patients with high-risk localized prostate cancer were enrolled into a phase I-II clinical trial of neoadjuvant chemotherapy with docetaxel and mitoxantrone followed by prostatectomy. Pre-treatment prostate tissue was acquired by needle biopsy and post-treatment tissue was acquired by prostatectomy. Prostate cancer gene expression measurements were determined in 31 patients who completed 4 cycles of neoadjuvant chemotherapy. We identified 141 genes with significant transcript level alterations following chemotherapy that associated with subsequent biochemical relapse. This group included the transcript encoding monoamine oxidase A (MAOA). In vitro, cytotoxic chemotherapy induced the expression of MAOA and elevated MAOA levels enhanced cell survival following docetaxel exposure. MAOA activity increased the levels of reactive oxygen species and increased the expression and nuclear translocation of HIF1α. The suppression of MAOA activity using the irreversible inhibitor clorgyline augmented the apoptotic responses induced by docetaxel. In summary, we determined that the expression of MAOA is induced by exposure to cytotoxic chemotherapy, increases HIF1α, and contributes to docetaxel resistance. As MAOA inhibitors have been approved for human use, regimens combining MAOA inhibitors with docetaxel may improve clinical outcomes.